Toxicity of Piper hispidinervum Essential Oil to Callosobruchus maculatus and Cowpea Bean Quality - Maria Suely Siqueira Ferraz; Lêda Rita D’Antonino Faroni; Adalberto Hipólito de Sousa; Fernanda Fernandes Heleno; Marcus Vinicius de Assis Silva; Ernandes Rodrigues de Alencar (Plants)
Essential oils and their major compounds have been studied to protect stored grains, especially for the control of insects. In this context, this research aimed to investigate the fumigation and contact toxicities of the essential oil of Piper hispidinervum C. DC. (Piperaceae) (sin. Piper hispidum Sw.) to Callosobruchus maculatus adult individuals and the effect on insect progeny. We also assessed the essential oil’s effect on stored-cowpea quality. The fumigation bioassay used essential oil at 14.3, 57.1, 100.0, 142.9, and 185.7 µL/L of air, whereas the contact bioassay tested concentrations of 60, 80, 100, 120, and 140 µL/kg. Insect mortality was appraised after four days (fumigation) or one day (contact). In turn, oviposition and emergence rates were evaluated after seven (fumigation) or fifty (contact) days of storage. Grain quality was also analyzed after 50 days of storage. Safrole was confirmed as the primary compound of the essential oil. P. hispidinervum essential oil proved its fumigant and contact toxicities to C. maculatus adult individuals. The concentrations lethal to 50 and 95% of the population were, respectively, 91.23 and 242.59 µL/L of air (fumigation) and 101.51 and 208.52 µL/kg of cowpeas (contact). In both application forms, C. maculatus oviposition and progeny rates declined with the increase in the essential oil concentration. Furthermore, cowpea bean quality was preserved even at sublethal doses.